Characteristics and Treatment Responses of Rheumatoid Arthritis Patients at Dr.Cipto Mangunkusumo National General Hospital - Rudy Hidayat (Indonesian Rheumatology Associantion, 2023)
Introduction. Rheumatoid arthritis (RA) is a chronic progressiveautoimmune rheumatic disease that primarily affects the joints. The goal ofRA treatment is to achieve remission or low disease activity, using a treatto-target approach. This study aims to explore the characteristics of RApatients and evaluate their treatment responses in Dr. CiptoMangunkusumo National General Hospital (RSCM). Methods. This crosssectionalstudyisconductedbycollectingdemographicandclinicaldata,as wellasinterviewingadultpatientsthathavebeendiagnosedwithRAatthe Rheumatology Clinic of RSCM and have been on disease-modifyingantirheumatic drugs (DMARD) treatment for a minimum of 6 months.Results. A total of 94 patients were included in this study. Subjects werepredominantly female (93.6%) and had no formal jobs (64.9%). A majority ofRA patients exhibited moderate disease activity (48.9%, based on DiseaseActivity Score-28 with erythrocyte sedimentation rate [DAS-28 ESR]), with arelatively high level of steroid use (86.2%). Notably, most patients startedDMARD treatment more than 2 years after the onset of symptoms (45.7%).The proportion of patients achieving therapy target (remission to low diseaseactivity) was 41.5%, with 13.8% attaining remission. Furthermore, HealthAssessment Quality (HAQ) scores were found to be significantly lower amongthe target-achieving group, indicating better quality of life. Conclusion.Therapy target was achieved in 41.5% of RA patients in RSCM, with 13.8%achieving remission. Further research can be conducted to evaluate factorswhich may affect treatment response among RA patients.